THE EFFECT OF PARENTS ROLE TOWARDS THEMATIC LEARNING OUTCOMES OF CLASS V STUDENTS - Andreas Au Hurit; Nur Eka Lestari; Agus Kichi Hermansyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The role of parents is one of the factors that affect students’ learning outcomes so the purpose of this study is to determine the effect of the role of parents on students thematic learning outcomes of class V of MI Al-Ma'arif Merauke. This research was a quantitative correlation and expose facto research conducted at MI Al-Ma'arif Merauke. The subjects of this study were students of class V B MI AL-Ma'arif totaling 32 students. Data collection techniques used were questionnaires and documentation. The instruments used were questionnaire sheets and documents. While the data analysis techniques used were correlation test, hypothesis test (t). Calculation of hypothesis testing used SPSS version 21 using the product moment correlation formula. The results showed that there was a relationship between the role of parents on students' thematic learning outcomes, this was indicated by the results of the correlation coefficient of 0.389 > rtable of 0.349 and a significance level of 0.028 < 0.05 with a low level of influence. t test results revealed that the t value of 2.310 > ttable 2.042 with a significance value of 0.028 < 0.05 and the results of the coefficient of determination (r2) of 15,1%, this shows there is an effect of the role of parents on the thematic learning outcomes of students.